2015
DOI: 10.1016/j.envres.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal urinary arsenic species and infant cord blood leptin levels in a New Hampshire Pregnancy Cohort

Abstract: Leptin is an important pleiotropic hormone involved in the regulation of nutrient intake and energy expenditure, and is known to influence body weight in infants and adults. High maternal levels of arsenic have been associated with reduced infant birth weight, but the mechanism of action is not yet understood. This study aimed to investigate the association between in utero arsenic exposure and infant cord blood leptin concentrations within 156 mother-infant pairs from the New Hampshire Birth Cohort Study (NHB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 52 publications
0
6
2
Order By: Relevance
“…We also observed a negative association between prenatal As and Sb and child leptin. One study found a positive association between maternal urinary As and cord blood leptin 34 , in contrast to the negative association observed here. To our knowledge there are no studies to date examining the impact of prenatal Sb on cardio-metabolic risk.…”
Section: Discussioncontrasting
confidence: 99%
“…We also observed a negative association between prenatal As and Sb and child leptin. One study found a positive association between maternal urinary As and cord blood leptin 34 , in contrast to the negative association observed here. To our knowledge there are no studies to date examining the impact of prenatal Sb on cardio-metabolic risk.…”
Section: Discussioncontrasting
confidence: 99%
“…Arsenic may also modulate expression of two arsenic-related genes ( AQP9 , ENPP2 ) in the placenta that are involved in arsenic transport and regulation of angiogenesis, respectively ( Fei et al 2013 ). The hormone leptin, which regulates appetite and metabolism, may also be involved: Positive associations have recently been reported between prenatal arsenic and cord blood leptin ( Gossai et al 2015 ), and cord blood leptin was negatively associated with length and head circumference at birth, as well as with lower weight gain from birth to 4 months, in 136–197 infants in the ALSPAC (Avon Longitudinal Study of Parents and Children) cohort ( Ong et al 1999 ). Cord blood leptin was also associated with lower BMI z -score, lower height-for-age z -score, and shorter leg length in 3-year-old children in the Project Viva cohort ( Mantzoros et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that the increased level of leptin in umbilical cord blood was related to high birth weight and also to the risk of obesity in future (Ahmed et al, 2011). Further works have also proved that exposure to low dose arsenite (up to 2 mM) for 8 weeks decreased glucose transporter type 4 (GLUT-4) expression upon insulin stimulation in 3T3-L1 adipocytes primed to differentiate (Gossai et al, 2015). An invitro study indicated that incubation of adipocytes with arsenic disrupts multiple metabolic pathways.…”
Section: Experimental Studiesmentioning
confidence: 99%